ANALYSIS OF THE INFLUENCE OF HEALTH EDUCATION TO IMPROVE MOTHER'S KNOWLEDGE IN PREVENTING STUNTING IN MASOLAKA RAYA SUB-DISTRICT, BOMBANA DISTRICT: HEALTH EDUCATION AND STUNTING - Yulfiah Suleman; Tasnim Tasnim; Herianto Wahab (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:Data The Bombana Health Office stated that the details of stunting cases in 19 Districts were highest in Central Kabaena District with 160 cases, Central Kabaena 120 cases, Masolaka Raya 57 cases, North Poleang 54 cases, and the lowest was Mataoleo District. The purpose of this research isto analyze the effect of health education in efforts to prevent stunting through changes in knowledge, attitudes and actions of mothers of children under five in Masolaka Raya District, Bombana Regency. Methods:The research conducted was a quasi-experimental study with a non-equivalent control group design. The population in this study amounted to 159 people. The sample size was 114 people. The data were processed using the Wilcoxon signed rank test and the Kruskal Wallis H. test. Result:Based on the test results with the Wilcoxon signed rank test, the significance value shows the value of p-value = 0.000 <? = 0.05 for all health education methods to increase the knowledge of mothers under five in preventing stunting in Masolaka Raya District, Bombana Regency. Conclusion:There is an effect of health education with the lecture method, lecture method and leaflet, lecture method and video on increasing the knowledge of mothers under five in preventing stunting in Masolaka Raya District, Bombana Regency.